2001
DOI: 10.1046/j.1442-200x.2001.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

Severe upper airway obstruction in the tropics requiring intensive care

Abstract: There is marked heterogeneity in the causes of upper airway obstruction in the tropics with viral croup remaining the most common. A significant proportion required ventilation, but outcome is generally favorable, except in those with bacterial tracheitis and mediastinal malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Diseases leading to severe compromise of the upper airway are the most frequent causes of cardiac arrest in pediatric population. In one study, severe upper airway obstruction accounted for 3.3 % of all pediatric intensive care unit (PICU) admissions [1].…”
Section: Introductionmentioning
confidence: 99%
“…Diseases leading to severe compromise of the upper airway are the most frequent causes of cardiac arrest in pediatric population. In one study, severe upper airway obstruction accounted for 3.3 % of all pediatric intensive care unit (PICU) admissions [1].…”
Section: Introductionmentioning
confidence: 99%
“…The study involved 160 patients out of a total number of 8560 patients seen within the study period giving a prevalence of 1.87%. In an earlier similar study in 2001, Chan et al found a prevalence of 3.3% [14]. This difference may stem from patient selection because they studied mainly patients requiring intensive care.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that severe upper airway obstruction can be a reason for paediatric ICU admission. It accounts for 3.3% of such admissions [14]. Conservative medical therapy which included antibiotics, corticosteroids, decongestants, vitamins was employed in some of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…• Croup: Administer adrenaline (epinephrine) (1 mg/mL) 0.5 mL/kg (maximum dose 5 mL) in 3 mL NS via nebulizer PRN, repeat PRN, 24 dexamethasone 0.6 mg/kg oral/in-tramuscular (IM)/intravenous (IV) Â 1 dose (maximum dose 16 mg) 24 • Airway edema (allergy associated): Adrenaline (epinephrine) (1 mg/mL) 0.5 mL/kg (maximum dose 5 mL) in 3 mL NS via nebulizer, repeat PRN, 24 32 ; Unconscious: open airway, remove visible foreign body, avoid blind finger sweep, perform compressions/ventilations, 32 consider bronchoscopy, 18,33,34 and consider tracheostomy. 18,33,[35][36][37] Lower Airway Obstruction If a regular spacer device is not available for use with the MDI, consider use of a sealed-soda bottle as a suitable alternative. 40 Attach a face mask to the cap end for use in infants.…”
Section: Upper Airway Obstructionmentioning
confidence: 99%